2016
DOI: 10.1097/mpg.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

One Extra Gram of Protein to Preterm Infants From Birth to 1800 g

Abstract: Increasing AA/protein intake both during parenteral and enteral nutrition does not improve growth and neurodevelopment of small preterm infants 500 to 1249 g birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 26 publications
4
51
1
Order By: Relevance
“…Burattini et al [24], Clark et al [16], Vlaardingerbroek et al [13], Blanco et al [33,34,35]. and Bellagamba et al [23] reported actual rates in gram per kilogram per day. A meta-analysis including these 5 studies showed no differences between the intervention and control groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Burattini et al [24], Clark et al [16], Vlaardingerbroek et al [13], Blanco et al [33,34,35]. and Bellagamba et al [23] reported actual rates in gram per kilogram per day. A meta-analysis including these 5 studies showed no differences between the intervention and control groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, a lack of consistency in the timeline of this outcome could have influenced the results. Vlaardingerbroek et al [13], Clark et al [16], and Blanco et al [33,34,35] reported mean weight gain for the first 28 days, Burattini et al [24] compared mean weight gain at 36 weeks postmenstrual age (PMA), and Bellagamba et al [23] reported mean weight gain rates from birth and regain of BW to 1,800 g (54 days in both groups). Scattolin et al [26] also reported growth rates, but only for the 2nd and 3rd week of life separately and was, therefore, not included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations